Nearly Degenerate Four-Wave Mixing in Single-Mode Fabry–Pérot Laser Diode Subject to Single Beam Optical Injection - Jian-Wei Wu; Yong Hyub Won (IEEE Photonics Journal)
In this paper, nearly degenerate four-wave mixing created by pump–probe structure with small frequency spacing and enough high power is demonstrated and discussed by introducing single optical beam into single-mode Fabry–Pérot laser diode, in which the injected beam is called the probe wave, whose frequency detuning is controlled within ±50 GHz, and lasing resonance mode such as dominant mode or arbitrarily residual side mode is selected as the pump wave. In the case of dominant mode like the pump wave, conjugate signals around the pump–probe wave are easily observed for positive and negative probe detuning by judiciously tuning injected probe power. While external injection mode is moved towards the side mode selected as the pump wave, newly generated signals only occurred with small positive probe detuning. As the probe wave with positive frequency detuning is close to the pump wave, higher order conjugate signals are gradually grown. Under the condition of side mode as the pump wave, the strongly nonlinear mixing of the pump–probe wave also gives rise to new frequency signals on both sides of the dominant mode with enough high peak level. Against the change of correspondingly initial power and frequency detuning of the probe wave, outcome spectrum, output power, and conversion efficiency of conjugate signals are analyzed in detail, while dominant or one side mode is, respectively, selected as the pump wave.